THE PROBLEM OF EMPATHIC ABILITIES IN PSYCHOLOGY - Omonova S.M. (Galaxy International Interdisciplinary Research Journal, 2023)
This article is devoted to the problem of empathic abilities in psychology. Also in the topic of the article, empathic skills and theoretical and practical problems of their study, empathy and emotional intelligence, levels of empathy are widely covered.